2018
DOI: 10.1093/milmed/usy232
|View full text |Cite
|
Sign up to set email alerts
|

Diet Macronutrient Composition, Physical Activity, and Body Composition in Soldiers During 6 Months Deployment

Abstract: Carbohydrate intakes and physical activity were low, compared with the general recommendations. Protein intakes were relatively high. Skeletal muscle mass and subcutaneous fat increased. Suboptimal diet together with low level of physical activity may have a negative impact on body composition, physical performance, and cardiometabolic health. Consequently, soldiers should be encouraged to consume more fiber-rich carbohydrates and less saturated fatty acids as well as maintain a high level of physical fitness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Furthermore, the present body composition and blood biomarker results did not reflect disturbances in hormonal balance either in the HiR or LoR group. These findings are supported by previously published results of rather low physical activity and work load [26], as well as well-maintained energy balance [27] during the same crisis management operation. Thus, there were no environmental or physiological barriers for the training adaptations during the operation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the present body composition and blood biomarker results did not reflect disturbances in hormonal balance either in the HiR or LoR group. These findings are supported by previously published results of rather low physical activity and work load [26], as well as well-maintained energy balance [27] during the same crisis management operation. Thus, there were no environmental or physiological barriers for the training adaptations during the operation.…”
Section: Discussionsupporting
confidence: 91%
“…During the study, the soldiers performed their operative duties including typical military tasks, such as patrolling and observing outside the military base, as well as maintenance and headquarter duties inside the base. Recently, a more detailed description of the physical activity and work load [26] of the participants as well as their diet [27] has been published. Sixty-six voluntary male soldiers who were deployed for a crisis management operation in the Middle East took part in the baseline measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, within BMI/WHR high groups, about 80% of either BMI-or WHR-high Chinese soldiers were BFP low ( Table 6), suggesting that BMI and WHR did not reflect the real fat content for most BMI high and WHR high military personnel. For military personnel, high protein diet and intensive military training have positive effects on the improvement of fat-free mass and skeletal muscle [62,63]. A Finland study also showed increased lean tissue was observed in soldiers through military service [14].…”
Section: Discussionmentioning
confidence: 99%
“…The studies included test persons from the Navy (Choi et al 2010;Tharion et al 2004) and the Air Force (Scott et al 2007). In the paper of Schulze et al (2015), test persons from both the army and the air force had been examined, and in three studies (Aandstad et al 2016;Nykanen et al 2019;Wyss et al 2012), an allocation to the individual Services was not possible due to lacking data. In addition to this, the studies were conducted all in different countries: Germany (Schulze et al 2015), England (Scott et al 2007), Finland (Nykanen et al 2019), Norway (Aandstad et al 2016), Switzerland (Wyss et al 2012), South Korea (Choi et al 2010) and the USA (Tharion et al 2004).…”
Section: Resultsmentioning
confidence: 99%